El bienestar subjetivo de los LGB (lesbianas, gays y bisexuales) en la Universidad Nacional de Trujillo, Trujillo 2016. - Vásquez Campoverde, Carolina (2018)
This research aims at describing the subjective well-being of the LGB in the UNT, taking into account the degree of adaptability and family cohesion, as well as the social support with which the homosexual people count in the National University of Trujillo. Its specific objectives are to describe the subjective well-being of LGTBs in their affective and cognitive components that are determined by a gender condition and influence their personal and social experiences. The research was conducted with a sample of 20 students belonging to the LGB movement. To identify the participants, information was taken from the existing database in the collectives that are accessed as Inadis La Libertad and Epicentro Trujillo, choosing students that are representative by school, which are a total of 42, of which studied 48% from a quantitative and qualitative perspective. 48% of the participants in this report volunteered to be part of the study. The evaluation makes an analysis of the concept of subjective well-being. Initially an annotation of the term is carried out from a historical perspective, analyzing its integrating elements. Among these, its affective-emotional and cognitive-rational components stand out, identified respectively with measures of affective balance and life satisfaction. Along with this affective-cognitive dimension, other positive-negative and internal-external-are taken into account, as well as all those variables that influence subjective well-being, grouped in the following categories: health and sociodemographic variables, individual characteristics, variables of behavior and life events; for this, the inductive - deductive, analytical - synthetic, statistical and phenomenological methods were used; the techniques of direct observation, in-depth interview, and review of bibliographical sources and instruments such as interview guide and global satisfaction test with life and subjective happiness test. The results show that in general the students are satisfied with their life, with the family being the main source of happiness. It was found that participants with a partner are happier and more satisfied than single women. Regarding general and physical health, there are no differences between men and women, however, men present a more negative evaluation than women regarding their health. emotional. Neither men nor women would leave or change careers if they could. Finally, a direct and significant relationship was found between happiness, self-concept and life satisfaction Through this report, we can demonstrate the progress of the LGB collective, as well as the need to design social programs that positively impact the well-being experienced by people.